Supply chain quality risk management: an empirical study of its dimensions and impact on firm performance - Tse, Ying Kei (2012)
The goal of this dissertation is to understand what supply chain quality risk management (SCQRM) is and how SCQRM can help firms improve product quality and firm performance. This dissertation attempts to reveal and understand the SCQRM practices in order to provide new insights in dealing with supply chain quality risk. Thus, this dissertation aims to address three research questions: RQI) What should SCQRM entail in order to reduce the risk to the quality of products being handled along the supply chain? RQ2) What would a valid measurement scale of SCQRM entail? RQ3) What is the impact of SCQRM on product quality and firm's performance?